Imagens públicas em disputa : o governo João Goulart através da grande imprensa carioca (1961-1964) - Corrêa, Cristiane Mitsue (2018)
The research aims to analyze the construction of the public image of President João Goulart and his government (1961-1964) through the press in Rio de Janeiro - Correio da Manhã, Jornal do Brasil and Última Hora. Three political moments are analyzed that marked different phases and moments of the government: inauguration of Goulart, in 1961; referendum for return of presidentialist regime or maintenance of parliamentary system, in 1963; and reform meeting, in 1964. The aim is to analyze and understand how newspapers elaborated president's public image on political events that had in common the discussion of categories such as democracy, citizenship and popular participation, located in periods of political, economic and military crisis. In this study, when analyzing the journalistic discourses and the changes of opinion of press according to the political events, the importance of production of press in our perception of the social, political and historical reality is considered, determining a look on the past.